Short-Term Impact of Point-Source Enrichment on the Behavior of Gestating Sows Housed in Groups - Zhitnitskiy, Perle E.; Terreaux, Claire M. H. A.; Phillips, Hannah N.; Ventura, Beth A. (Frontiers in Animal Science, 2021)
Environmental enrichment is an important strategy to improve the welfare of farm animals. However, relatively little is known about enrichment for gestating sows, especially those raised on farms with slatted floors and for which provision of straw may be difficult. The objective of this study was therefore to investigate the short-term (4d) impact of a point-source enrichment object on the behavior of gestating sows housed in group pens. Four pens of gestating sows on a university research farm were randomly allocated to receive either enrichment or no enrichment (control) in a 2 by 2 crossover design. Time budgets were established by video recording focal sows’ behaviors (n=10 focals per pen) every 15 minutes between 0800 and 1500 every day. Enrichment use was further characterized by continuous behavior sampling for a 1h interval between 0830 and 0930 each day. The impact of parity, lameness and presence of stereotypical behavior such as sham chewing on enrichment use was evaluated. Over the course of the study, focal sows spent approximately 73% of observations inactive (either lying down (70%), standing (2%), or sitting (1%)). Within the remaining observations, sows were most commonly observed sham-chewing (16%), followed by 3% exploring, 2% feeding, 2% walking and 1% interacting with the enrichment when it was available. Low-parity sows, moderately-lame sows, and sows observed sham chewing at baseline displayed more consistent enrichment use over the course of the study (p=0.02, p<0.01, p=0.04, respectively). While no adverse behavioral effects (increased agonism or sham chewing) due to provision or removal of the enrichment object were observed and while eighty-five percent of sows were observed to interact with enrichment at least once, interest declined sharply after the first day. We conclude that further research is needed to identify effective and sustainable enrichment strategies for gestating sows.